2017
DOI: 10.24953/turkjped.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations between anthropometric characteristics and insulin markers in mothers and their neonates and with neonate`s birth weight: An observational cohort study

Abstract: Naseh A, Nourbakhsh S, Tohidi M, Sarkhail P, Najafian B, Azizi F. Associations between anthropometric characteristics and insulin markers in mothers and their neonates and with neonate`s birth weight: An observational cohort study. Turk J Pediatr 2017; 59: 625-635. This study aimed to identify possible associations between anthropometric characteristics and insulin markers of mothers and 1) their neonate`s birth weight, and 2) those markers of neonates. A prospective observational cohort of 100 healthy mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Our finding of no association between maternal IR and birth weight agrees with a report by Bomba-Opon et al [ 31 ] among Polish mothers and babies and a prospective study among Turkish mothers and their infants [ 11 ]. In contrast, a retrospective database review of second-to-third trimester healthy pregnant Japanese mothers by Yamashita et al [ 18 ] found maternal HOMAIR to be positively associated with birth weight and LGA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of no association between maternal IR and birth weight agrees with a report by Bomba-Opon et al [ 31 ] among Polish mothers and babies and a prospective study among Turkish mothers and their infants [ 11 ]. In contrast, a retrospective database review of second-to-third trimester healthy pregnant Japanese mothers by Yamashita et al [ 18 ] found maternal HOMAIR to be positively associated with birth weight and LGA.…”
Section: Discussionsupporting
confidence: 93%
“…Maternal obesity, excessive intrapregnancy weight gain and maternal IR independently, but variably, impair fetal growth and adiposity and birth size [ 8 - 11 ]. Impaired fetal growth (IFG) (which includes wasting or stunting) or excessive fetal growth (EFG) (macrosomia or large-for-gestational-age [LGA] birth) increases the risk of cardiometabolic disorders intergenerationally [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been found that even when the recommended plans are well followed, the pregnancy outcomes cannot be effectively improved [15]. Some researches ascribes this to IR [16] and the heterogeneity of IR in pregnant women with GDM somehow results in different outcomes [11,17]. Therefore, more exploration on the relationship between IR in the second trimester (24-28 weeks) and adverse pregnancy outcomes in GDM women may help identify women who are at high risk of these adverse outcomes, and management can therefore be carried out in early pregnancy even pre-pregnancy, sometimes adding insulin sensitization therapy if necessary to improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been found that even when the recommended plans are well followed, the pregnancy outcomes cannot be effectively improved (3). Some researches ascribes this to insulin resistance IR (4) and the heterogeneity of IR in pregnant women with GDM somehow results in different outcomes (5,6). Therefore, more exploration on the relationship between IR in the second trimester (24-28 weeks) and adverse pregnancy outcomes in GDM women may help identify women who are at high risk of these adverse outcomes, and management can therefore be carried out in early pregnancy even pre-pregnancy, sometimes adding insulin sensitization therapy if necessary to improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%